2020
DOI: 10.1021/acs.jproteome.0c00245
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Penetration Enhancers Increase Hydrogen Peroxide Uptake in C. elegans for In Vivo Fast Photochemical Oxidation of Proteins

Abstract: Fast photochemical oxidation of proteins (FPOP) is a hydroxyl radical protein footprinting method that covalently labels solvent-accessible amino acids by photolysis of hydrogen peroxide. Recently, we expanded the use of FPOP for in vivo (IV-FPOP) covalent labeling in C. elegans. In initial IV-FPOP studies, 545 proteins were oxidatively modified in all body systems within the worm. Here, with the use of chemical penetration enhancers (CPEs), we increased the number of modified proteins as well as the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…Animals were grouped as mentioned in Table S2; AMY and AMYDOPA were applied on the epilated dermal side of animal skin by gentle rubbing and kept undisturbed. Skin irritancy caused by hydrolytic enzymes could be reduced by liposome coating, which prevents direct contact with skin . Infact, enhanced permeation of dextrans and insulin observed through the intercellular pathway and hair follicular route after trypsin treatment caused low skin irritation .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals were grouped as mentioned in Table S2; AMY and AMYDOPA were applied on the epilated dermal side of animal skin by gentle rubbing and kept undisturbed. Skin irritancy caused by hydrolytic enzymes could be reduced by liposome coating, which prevents direct contact with skin . Infact, enhanced permeation of dextrans and insulin observed through the intercellular pathway and hair follicular route after trypsin treatment caused low skin irritation .…”
Section: Resultsmentioning
confidence: 99%
“…Skin irritancy caused by hydrolytic enzymes could be reduced by liposome coating, which prevents direct contact with skin. 56 Infact, enhanced permeation of dextrans and insulin observed through the intercellular pathway and hair follicular route after trypsin treatment caused low skin irritation. 57 However, in our study, there were no signs of allergic bleeding and lump formation of edema on the animal skin even after 24 h. We achieved maximum penetration of collagen within 15 min after treatment with 0.5 U of AMYDOPA.…”
Section: 3mentioning
confidence: 99%
“…This approach facilitates protein labelling within organelles and, in the case of C. elegans, within whole organisms, enabling structural interrogation under native conditions. [110][111][112]…”
Section: Hydroxyl Radical Footprinting-mass Spectrometry (Hrf-ms)mentioning
confidence: 99%
“…65,67,322 The FPOP derivative of HRF-MS has had similar in cell success over recent years, with a 2019 paper from Espino and Jones applying technique in vivo to determine protein solvent accessibility in C. elegans. [110][111][112] Given the prevalent use of C. elegans as a model organism, development of this workflow has exciting potential for the future study of disease mechanisms. The development of in vivo structural MS, however, is not limited to the peptide-based techniques, as developments have also been made in an attempt to bring protein-based methods into cells.…”
Section: Moving Structural Biology Towards In Cell Analysismentioning
confidence: 99%
“…Reagent access to the cells or organisms is one of the more challenging aspects of CL-MS experiments, yet it is essential to control as it largely determines the labeling efficiency, especially for the intracellular side of membrane proteins and for multicellular organisms. Jones and co-workers have found that the addition of CPEs can increase the uptake of labeling reagents via mild disruption to the lipid bilayer (Espino, Zhang, & Jones, 2020). These CPEs should not be toxic to the cell or organism within the working concentrations and ideally should not interfere with the labeling reagent.…”
Section: Chemical Penetration Enhancers (Cpes)mentioning
confidence: 99%